Just pay and you can get your certificate - Abd Razak, Dzulkifli (2006)
Exam certificates are being forged. Pay slips are being forged. Now even some higher education institutes are coming under suspicion and may taint the good name of Malaysian higher education. THIS is the time of the year when students, teachers and parents will be holding their breath in anticipation of public examination results. It is a stressful time given the nation’s preoccupation with the number of As one can score as this seems the absolute hallmark of success. It was, therefore, not surprising to find out from a news report recently that forgeries and fraudulent practices are prevalent, driven by blind fascination with the paper chase and a string of As. The demand has spun a new type of business where you can better your grade or certificate of choice on demand. Digital printing shops and freelance designers are putting their talents to fraudlent use to "upgrade" examination results.